A comparison of He and Ne FIB imaging of cracks in microindented silicon nitride - Zhang, Hongzhou (My University, 2018)
Helium ion microscopy (HIM) offers potential as a high spatial resolution technique for imaging insulating samples that are susceptible to charging artifacts. In this study helium and neon ion microscopy are used to image cracking in microindented samples of the non-conductive ceramic silicon nitride. The crack morphology of radial cracks emanating from the microindentations has been characterized for two different compositions of silicon nitride, with and without conductive coatings. Gold coating enhances crack edge contrast, but masks grain contrast for both He and Ne ion-induced secondary electron (ISE) imaging. Carbon coating enables the crystalline and glassy phases to be distinguished, more clearly with Ne-ISE, and the cracking pathway is found to be primarily intergranular. Zones of <100 nm diameter depleted ion-induced secondary electron emission along the crack paths are identified, consistent with charging ‘hotspots’.
Keywords: Helium ion microscopy (HIM); Ceramic silicon nitride; Microindentations; Gold coating; Electron emission; Carbon coating